Yoga’s effects on athletes’ balance and coordination - Prit Pal; Dr. Atul Shukla (Innovative Research Thoughts, 2022)
Yoga improves athletes' balance and coordination via mental concentration and self-awareness. This ancient practise of mindful movements, breathing, and meditation may improve an athlete's performance by strengthening the mind-body connection. Incorporating yoga into an athlete's training programme helps enhance proprioception, the body's capacity to feel its location and motions in space. Athletes improve their proprioception and body awareness via balancing. This increased awareness decreases the danger of injury from slips or awkward landings and sharpens their responsiveness to abrupt environmental changes during competition. Yoga helps athletes focus and concentrate. In high-stakes competitions, athletes must be cool and focused to perform well. Yoga helps players focus and filter out distractions. This mental clarity helps individuals coordinate their motions and activities better. Yoga emphasises pranayama, or breath control. Pranayama helps athletes control their breathing during heavy exercises to give oxygen to muscles and essential organs. Controlled breathing boosts endurance and relaxes the nervous system, lowering tension and anxiety that may impair coordination and balance. Yoga improves flexibility and suppleness. Athletes may move more freely by stretching and posing. Flexibility prevents muscle imbalances, improving complicated movement coordination. Yoga improves athletes' balance and coordination beyond physical activity. Yoga helps athletes succeed by increasing bodily awareness, mental concentration, breathing control, and flexibility. Athletes may attain new levels of ability and success by incorporating yoga into their training.